Genetic diversity of two evergreen oaks (Quercus suber L. and Q (ilex) rotundifolia Lam.) in Portugal using AFLP markers - Coelho, A. C. (2012)
The genetic variability of cork oak (Quercus suber, L.) in Portugal was evaluated by AFLP using five primer combinations. Three hundred and thirteen trees from three geographically contrasting regions exhibited a high level of genetic variation. The genetic profile of each individual is composed of 291 loci, randomly positioned in the genome and consists of monomorphic and polymorphic fragments. Similarities and dissimilarities among the individuals were quantitatively evaluated by numerical taxonomy. The overall sample shows a proportion of AFLP polymorphic markers of 71%, denoting a high level of variability. Ninety percent of the polymorphic markers identified in cork oak genotypes are uniformly distributed throughout the cork oak populations of Algarve, Alentejo and Trás-os-Montes regions. The coefficients of genetic similarity vary from 0.61 to 0.88 implying that 60% of fragments found are common. A sample of 52 holm oak [Quercus ilex subsp. rotundifolia (Lam.)] trees from overlapping areas was also analysed by AFLP with the same five primer combinations. However the codification of markers together with those selected on cork oak profiles was feasible with only one primer combination due to an apparent much higher polymorphism. AFLP and numerical taxonomy analysis enabled to differentiate the taxa and showed that the level of similarity observed between the profiles of the individuals from holm oak species was lower than that observed in cork oak, implying that apparently the degree of polymorphism is higher in Q. ilex subsp. rotundifolia than that quantified in Q. suber. A Bayesian approach was used to assess Q. suber total genetic diversity (Ht = 0.2534, P < 0.001) of which 1.7% (Fst = 0.0172, P < 0.001) was assigned to differences among populations. Analysis of molecular variance (AMOVA) showed that most genetic variation is comprised within populations (96%) while 3.6% is among populations (Φst = 0.036, P < 0.001). Differences among populations within geographic regions account for 2.6% (Φsc = 0.026, P < 0.001) of the total variation and only 1.3% (Φct = 0.013, P = 0.007) is attributed to variation among regions denoting little differentiation of populations over a range of 700 km.